The organization of knowledge in multinational firms - Anna Gumpert (Deutsche Bundesbank, 2015)
This paper provides the first in-depth study of the organization of knowledge in multinational firms. The paper develops a theoretical model that studies how firms optimally split knowledge between their headquarters and their production plants if communication costs impede the access of production plants to headquarter knowledge. The paper assumes that the foreign plants of multinational firms face higher communication costs with headquarters than their domestic plants, and shows that multinational firms therefore systematically assign more knowledge to both their foreign and domestic plants than non-multinationals. This helps explain why multinational firms pay higher wages to their production workers than non-multinational firms, and why their sales and their investment probability decrease across space. Empirical evidence from data on corporate transferees confirms the model predictions for multinationals' organization of knowledge. Data on German multinational firms corroborate the implications of the model in relation to the geography of multinationals' sales and investments.
Keywords: D21; D24; F21; F23; 330; multinational firm; knowledge hierarchy; organization; geography of FDI; multinational wage premium; corporate transferees